PAI Teacher Skills in Class Management at SMK Negeri 3 Karawang - Deliana Dewi Sutowo; Amiruddin, Amiruddin; Iqbal Amar Muzaki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to find out how the teacher's skills in class management affect the learning of Islamic Religious Education. This research was conducted at SMK Negeri 3 Karawang. The research method used is a qualitative method and is inductive in nature, namely letting problems arise through existing data accompanied by notes from in-depth interviews and document analysis from the results of these interviews. The results of the study show that in order to create good classroom management, teachers are required to be able to have the skills: creating and maintaining an optimal learning climate, controlling learning conditions so that they are effective and efficient, managing classroom equipment, and managing socio-emotionality. This has an effect on students that there is an increase in achievement or student learning outcomes in the cognitive, psychomotor, and affective domains in learning Religious Education.